2011
DOI: 10.1177/0044118x11422546
|View full text |Cite
|
Sign up to set email alerts
|

Gay-Straight Alliances, Social Justice Involvement, and School Victimization of Lesbian, Gay, Bisexual, and Queer Youth

Abstract: Few studies have investigated school-based, positive development for lesbian, gay, bisexual, and queer (LGBQ) youth, despite knowledge of their heightened negative school experiences compared to heterosexual youth (e.g., school victimization). This study examines associations among participation in Gay-Straight Alliance (GSA)–related social justice activities, GSA presence, and GSA membership with victimization based on sexual orientation and school-based well-being (i.e., school safety, school belongingness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 29 publications
3
69
0
Order By: Relevance
“…Students in schools with GSAs report fewer homophobic remarks, less harassment and bullying based on sexual orientation or gender identity, are less likely to miss school because of feeling unsafe, and are more likely to feel a sense of belonging to their school (e.g., Toomey & Russell, 2013; Kosciw et al, 2014). In a state-wide study in Massachusetts, Szalacha (2003) found that the presence of a GSA (not necessarily membership or participation in it) was a strong predictive factor in perceived school safety for LGBTQ as well as heterosexual students.…”
Section: Sogi-focused Policies and Practicesmentioning
confidence: 99%
“…Students in schools with GSAs report fewer homophobic remarks, less harassment and bullying based on sexual orientation or gender identity, are less likely to miss school because of feeling unsafe, and are more likely to feel a sense of belonging to their school (e.g., Toomey & Russell, 2013; Kosciw et al, 2014). In a state-wide study in Massachusetts, Szalacha (2003) found that the presence of a GSA (not necessarily membership or participation in it) was a strong predictive factor in perceived school safety for LGBTQ as well as heterosexual students.…”
Section: Sogi-focused Policies and Practicesmentioning
confidence: 99%
“…With regard to LGBT youth, recent research has demonstrated the negative impact of peer victimization on psychological adjustment and how that serves as a pathway to poorer academic outcomes (Kosciw, Palmer, Kull, & Greytak, 2013). Yet, research has also documented how affirmative supports for LGBT students at school can contribute to better school climates for LGBT as well as the well-being and academic success of these students (Kosciw, Greytak, Palmer, & Boesen, 2014;Toomey & Russell, 2013;Toomey, Ryan, Diaz, & Russell, 2013).…”
Section: School Climate and Lgbt Studentsmentioning
confidence: 99%
“…Yet, few studies have considered what factors account for some settings’ and youths’ greater involvement in advocacy than others. Given that advocacy is associated with wellbeing (Toomey & Russell, 2013), it is essential to ensure that such activities match the needs and abilities of youth so that they can derive the most benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Attention to social justice has been limited in the general youth programs literature and in models specifying factors that promote youth participation in these programs (Eccles & Gootman, 2002). Considering the benefits of advocacy not only for GSA members but also non-members in their schools who may face discrimination (Russell et al, 2009; Toomey & Russell, 2013), more attention should be given to youths’ efficacy to engage in advocacy. Adult advisors should not assume youth feel as capable to lead these types of events as they do others (e.g., socializing).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation